Prognostic role of D-dimer level upon admission in patients with traumatic brain injury - Zhang, Jing (Medicine (Baltimore), 2018)
BACKGROUND: The aim of this study was to evaluate the prognostic role of D-dimer level upon admission in patients with traumatic brain injury (TBI) through performing a meta-analysis. METHODS: PubMed, Web of Science, Cochrane Library, and EMBASE were searched for potential eligible literature. The study characteristics and relevant data were extracted. Poor functional outcome was defined according to the Glasgow Outcome Scale (GOS ≤3). Odds ratios (ORs) with 95% confidence intervals (CIs) were pooled to estimate the predictive value of D-dimer for progressive hemorrhagic injury (PHI) and poor functional outcome at 3 months (3M GOS ≤3) in patients with TBI. RESULTS: Eleven studies with 2761 patients were included. Eight studies examined the predictive role of higher D-dimer level for the risk of PHI, and the pooled OR was 1.72 (95% CI, 1.23–2.42). Three studies examined the predictive role of higher D-dimer level for the risk of 3M GOS ≤3, and the pooled OR was 2.00 (95% CI, 0.87–4.59). Significant between-study heterogeneities were observed, and sensitivity analyses and subgroup analyses were performed. No significant publication bias was found. CONCLUSIONS: In conclusion, in patients with TBI, higher D-dimer level upon admission was associated with higher risk of PHI, yet no significant relationship was found between D-dimer level and the risk of 3M GOS ≤3. In the future, this readily available marker could help identify patients at risk and tailor management of these patients, thus reducing PHI and improving outcome.